ANALISA SIFAT MEKANIK KOMPOSIT EPOKSI DENGAN PENGUAT SERAT POHON AREN (IJUK) MODEL LAMINA BERORIENTASI SUDUT ACAK (RANDOM) - Basuki Widodo (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Composite represent a number of systems of multi phase is nature of alliance that is alliance matrix materials or fastener with lasing. Of the merger will yield composite materials which have the nature of mechanical and different characteristic of its material, so that can be planned a composite material which wanted. Coconut coir is found abundantly but it’s exploiting which still less, besides their mechanical properties of this fibre still hanging in doubt. Pursuant to consideration of matter above, hence research about composite with materials filler of fibre of palm tree so that can know the mechanical properties of the each fibre of palm tree composition and matrix. From result of research which to be got highest composite interesting strength equal to 5.538kgf/ mm2 heavy fraction fibre of palm tree 40 %. And highest interesting strength mean equal to 5.128kgf/mm2 heavy faction fibre of palm tree 40 %. Strength of highest composite impact equal to 33.395Joule/mm2 with strength of mean impact 11.132Joule/mm2 heavy fraction fibre of palm tree 40 %.